2020
DOI: 10.3329/birdem.v10i3.48701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic appendectomy versus open appendectomy in acute appendicitis in obese diabetic patients

Abstract: Background: Acute appendicitis (AC) is a common surgical problem requiring emergency hospitalization for urgent appendectomy. In case of diabetic patients, the incidence of developing acute appendicitis including its complications like abscess, gangrene and perforation is higher than non-diabetic. Day by day, laparoscopic appendectomy is having an improved outcome in non-diabetic and non-obese patients. The aim of this study was to compare the outcomes of laparoscopic appendectomy versus open appendectomy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Both laparoscopic appendectomy and open appendectomy are commonly prac sed in ter ary 1 care centres. The outcome in terms of dura on of surgery, length of hospital stay, pain, wound infec on reported by various [2][3][4][5][6] studies in different se ngs was different. We found the mean age of the open appendectomy group was 30±16.85 years and the laparoscopic appendectomy group was 33.47 ±13.29 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both laparoscopic appendectomy and open appendectomy are commonly prac sed in ter ary 1 care centres. The outcome in terms of dura on of surgery, length of hospital stay, pain, wound infec on reported by various [2][3][4][5][6] studies in different se ngs was different. We found the mean age of the open appendectomy group was 30±16.85 years and the laparoscopic appendectomy group was 33.47 ±13.29 years.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of appendectomy ma ers whether it is an open appendectomy or laparoscopic appendectomy. The outcome in terms of dura on of surgery, length of hospital stay, pain, and wound infec on reported by various studies [2][3][4][5][6] in different se ngs was different. A study found the postopera ve pain and hospital stay were less in 2 laparoscopic appendectomy than open appendectomy.…”
Section: Laparoscopic Appendectomy Is a New Technique Than Open Appen...mentioning
confidence: 99%
“…In the United States, there are approximately 750,000 LCs per year, and the trend is expected to increase. [2,3] Preoperative anxiety is a common phenomenon in patients undergoing preoperative evaluation. It refers to the process of gradually strengthening from the start of a specific operation to the beginning of the operation.…”
Section: Introductionmentioning
confidence: 99%
“…LC has improved outcomes compared to traditional open surgery and is considered the standard of care for the treatment of cholecystitis. In the United States, there are approximately 750,000 LCs per year, and the trend is expected to increase [2,3] …”
Section: Introductionmentioning
confidence: 99%